2019
DOI: 10.1111/nph.16275
|View full text |Cite
|
Sign up to set email alerts
|

Allometric scaling laws linking biomass and rooting depth vary across ontogeny and functional groups in tropical dry forest lianas and trees

Abstract: Summary There are two theories about how allocation of metabolic products occurs. The allometric biomass partitioning theory (APT) suggests that all plants follow common allometric scaling rules. The optimal partitioning theory (OPT) predicts that plants allocate more biomass to the organ capturing the most limiting resource. Whole‐plant harvests of mature and juvenile tropical deciduous trees, evergreen trees, and lianas and model simulations were used to address the following knowledge gaps: (1) Do mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
69
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 64 publications
(118 reference statements)
4
69
1
1
Order By: Relevance
“…It was hypothesized that because lianas use trees as support to grow, they would allocate less biomass to stems and potentially invest their resources in leaves to reach the canopy and also in roots to provide anchorage and to explore deeper soils in search for water and nutrients, especially during dry periods (Selaya et al , ; van der Heijden et al , ). Contrary to the general belief, Smith‐Martin et al found that mature lianas do not invest less in stem biomass and do not display deeper root systems when compared to deciduous and evergreen mature trees in a tropical dry forest. Their model simulations indicate coordination between belowground allocation and aboveground phenology, mainly related to water supply, where evergreen trees invest in deeper roots to sustain leaves for longer periods than deciduous trees and lianas, since the latter display shallower root systems.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…It was hypothesized that because lianas use trees as support to grow, they would allocate less biomass to stems and potentially invest their resources in leaves to reach the canopy and also in roots to provide anchorage and to explore deeper soils in search for water and nutrients, especially during dry periods (Selaya et al , ; van der Heijden et al , ). Contrary to the general belief, Smith‐Martin et al found that mature lianas do not invest less in stem biomass and do not display deeper root systems when compared to deciduous and evergreen mature trees in a tropical dry forest. Their model simulations indicate coordination between belowground allocation and aboveground phenology, mainly related to water supply, where evergreen trees invest in deeper roots to sustain leaves for longer periods than deciduous trees and lianas, since the latter display shallower root systems.…”
contrasting
confidence: 99%
“…714–726) dug deep into these questions by bringing together results from fieldwork, a common‐garden experiment, and also by incorporating their results in an individual‐based terrestrial biosphere model to test the effects of changing biomass allocation and the rules behind such patterns. While Smith‐Martin et al confirm some of the expectations regarding biomass allocation of lianas and trees in tropical dry forests, they also find surprising and important trends that contradict prevailing wisdom.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Liana physical advantages also extend belowground, potentially including deeper, more extensive root systems and faster capillary flow than trees (Ewers et al, 1991;Restom and Nepstad, 2001). However, recent data from Costa Rica suggest that liana roots extend no deeper than trees (Smith-Martin et al, 2019). Further liana advantages among some species also include increased tolerance to herbivores (Ashton and Lerdau, 2008) and release of allelopathic chemicals (Ladwig et al, 2012).…”
Section: (A) Competition With Treesmentioning
confidence: 99%